Dual‐Responsive Supramolecular Antimicrobial Coating Based on Host‐Guest Recognition - Wang, Yiting; Wang, Gangyang; Ni, Yifeng; Zhou, Jiahui; Wang, Shuaibing; Gu, Yucong; Zhang, Dong; Zheng, Si Yu; Wu, Zi Liang; Zheng, Qiang; Zheng, Jie; Yang, Jintao (Advanced materials interfaces, 2022)
The adhesion and proliferation of the bacteria on biomedical surfaces have posed a great threat to patients. Developing a class of renewable bactericidal surface with excellent bacteria release capability is crucial for elongating the service life of the biomedical devices. However, releasing the bacteria fast and frequently is usually a trade‐off with releasing them thoroughly and completely regenerating the surface. Herein, a temperature/light dual‐responsive antimicrobial coating is developed. The cyclodextrin (CD)‐contained antifouling macromolecule and the thermal‐responsive azobenzene‐contained macromolecule are assembled on the CDs‐modified surface, combined with additional silver nanoparticles. The surface exhibits low bacteria attachments of 9.30 × 105 cells cm−2 (E. coli, 120 h), high bactericidal efficiency of ≈96.3%. Meanwhile, ≈86.9% of the attached bacteria can be released from the surface rapidly in response to temperature, and the residues can be thoroughly removed by irradiating UV irradiation (release ratio ≈91.0%). The functions of the surface can be resumed by switching the host‐guest network via light regulation. The 3rd regenerated surface still maintains low bacteria density of 12.4 × 105 cells cm−2, bacteria killing ratio of ≈95.0%, and bacteria release rate of ≈95.7%. The work is supposed to provide a new insight into the design of multifunctional antibacterial surface and broaden their applications. An antimicrobial coating consisting of antifouling host polymer, thermal‐responsive guest polymer, and bactericidal Ag nanoparticles is prepared. The coating possesses great antifouling and bactericidal functions. The adhered bacteria could be released efficiently with a stimuli of temperature or light. The functions of the surface can be restored after cyclic use via rebuilding the coating by successive dissociation and re‐association of the host‐guest interactions.